Wearable Glucose Monitoring and Implantable Drug Delivery Systems for Diabetes Management. Issue 17 (30th April 2021) - Zhang, Jinyuan; Xu, Jian; Lim, Jongcheon; Nolan, James K.; Lee, Hyowon; Lee, Chi Hwan
Abstract: The global cost of diabetes care exceeds 1 trillion each year with more than 327 billion being spent in the United States alone. Despite some of the advances in diabetes care including continuous glucose monitoring systems and insulin pumps, the technology associated with managing diabetes has largely remained unchanged over the past several decades. With the rise of wearable electronics and novel functional materials, the field is well‐poised for the next generation of closed‐loop diabetes care. Wearable glucose sensors implanted within diverse platforms including skin or on‐tooth tattoos, skin‐mounted patches, eyeglasses, contact lenses, fabrics, mouthguards, and pacifiers have enabled noninvasive, unobtrusive, and real‐time analysis of glucose excursions in ambulatory care settings. These wearable glucose sensors can be integrated with implantable drug delivery systems, including an insulin pump, glucose responsive insulin release implant, and islets transplantation, to form self‐regulating closed‐loop systems. This review article encompasses the emerging trends and latest innovations of wearable glucose monitoring and implantable insulin delivery technologies for diabetes management with a focus on their advanced materials and construction. Perspectives on the current unmet challenges of these strategies are also discussed to motivate future technological development toward improved patient care in diabetes management. Abstract : Wearable glucose sensors can be integrated with implantable drug delivery systems for closed‐loop diabetes management to improve the quality of life for diabetic patients. This review article overviews the emerging trends and latest innovations of wearable glucose monitoring technologies and implantable therapeutics for diabetes management with a focus on their materials, designs, sensing mechanisms, and clinical implications.